PENGARUH AUTONOMI KERJA PADA KESEJAHTERAAN DAN EMOTIONAL LABOR SERTA DIMODERASI OLEH DUKUNGAN REKAN KERJA - , Eza Mega Kuswoyo, Dr. Harsono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to examine the relationship of each variable that has a different outcome in the context of the school environment so that this study used a confirmatory approach. The sampling technique used in this study using non probability sampling methods, namely purposive sampling. Sample criteria used is the teacher who served as homeroom and have a service life of at least one year. The sample size used in this study as many as 178 respondents and 176 valid respondents. The results of this study found that job autonomy has a positive effect on job satisfaction, coworker support shown to moderate the relationship between deep acting and job satisfaction, job autonomy has a positive effect on surface acting.